Aggregate emission intensity targets: Applications to the Paris agreement - Jinhua Zhao (Asian Development Bank Institute (ADBI), 2018)
We develop the concept of aggregate emission targets, which are goals for national emissions but do not dictate the forms of regulation used to achieve the goals. We compare aggregate emission intensity, quantity, and price targets adopted at the national level but implemented cost effectively at the firm level. We obtain simple ranking conditions that depend on the slope ratio of marginal emission damage and marginal abatement cost curves, and threshold parameters determined by the variance and covariance of GDP and business-as-usual emission. We apply the ranking conditions to the top 12 CO2 emitters with specific GHG targets in the Paris Agreement, and obtain a robust result that intensity targets dominate quantity targets for most of these nations.
Keywords: Q58; 330; aggregate intensity target; quantity target; price target; climate change; INDC; Paris Agreement